2014
DOI: 10.1177/2325957414535978
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions to Antiretroviral Therapy in HIV-Infected Patients at the Largest Public Hospital in Nicaragua

Abstract: Adverse drug reactions most frequently affected the central nervous system. No ADR was life threatening. The frequency of ADRs in this Nicaraguan patient population was less than that reported from other studies in resource-limited settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
0
10
1
Order By: Relevance
“…The surveillance data that was used did not have grading of the severity of ADRs. Some studies have graded the ADRs using the World Health Organization grading or the Hartwig scale to determine the level of severity to patients’ morbidity [10,19,31,32]. Not all the data in the database were used as some patients were registered into the surveillance system study long after they had already initiated on ART.…”
Section: Discussionmentioning
confidence: 99%
“…The surveillance data that was used did not have grading of the severity of ADRs. Some studies have graded the ADRs using the World Health Organization grading or the Hartwig scale to determine the level of severity to patients’ morbidity [10,19,31,32]. Not all the data in the database were used as some patients were registered into the surveillance system study long after they had already initiated on ART.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, considering the continuum of HIV care in Nicaragua, only 11.5% of people living with HIV are estimated to have suppressed viral load and this is strongly associated with a high ART abandonment rate (estimated over 30%) [ 13 ]. Approximately a third of all persons under ART receive their drugs through a single national referral center: Hospital Dr. Roberto Calderón Gutiérrez in Managua [ 15 ]. This center started ART administration in 2003 with the support of the Global Fund to Fight AIDS, Tuberculosis and Malaria, and functioned as reference center until 2007, when ART administration was decentralized.…”
Section: Introductionmentioning
confidence: 99%
“…On average, the hospital enrolls 250 new patients per year [ 16 ]. Most people starting on first line ART receive regimens composed by two NRTI and one NNRTI, mainly zidovudine (AZT) + (lamivudine) 3TC + efavirenz (EFV), and tenofovir (TDF) + emtricitabine (FTC) + EFV [ 15 , 17 – 19 ]. Protease inhibitors (mainly boosted lopinavir, LPV/r) are used as second line regimens.…”
Section: Introductionmentioning
confidence: 99%
“…The most common adverse effects based on organ system classification reported by the study participants in this study were CNS and PNS (62%), metabolic disorder (16.4%), gastrointestinal (8.6%), skin (9%), and others (4%). A similar study by Lorio et al also reported that central nervous system (45%), gastrointestinal (27%), and dermatologic (18%) were the major adverse effects in HIV patients [27]. This might be due to ART regimen.…”
Section: Discussionmentioning
confidence: 87%